2004
DOI: 10.1002/syn.20025
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of aluminum‐induced changes in synaptic ultrastructure in rats

Abstract: Some evidence suggests that aluminum is one of the risk factors in Alzheimer's disease (AD); however, there is no study on the relationship between the synaptic configuration changes and aluminum uptake. In the present study, 40 rats were fed with water solution aluminum for 3 months and the effects of aluminum on the Gray's type I synapses in hippocampus and frontal cortex of rats were quantitatively investigated by electron microscopy. The effects of aluminum on the ability to learn and memorize were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 24 publications
3
37
1
Order By: Relevance
“…A decrease trend of body weight was observed in Alexposed rats, especially in 0.6% AlCl 3 group (no decrement of food intake) comparing with that of the control rats, which was consistent with previous reports (Hermenegildo et al, 1999;Jing et al, 2004). Meanwhile, it was shown that hippocampus, brain coefficients and hippocampus/ brain ratio in Al-exposed rats reduced gradually with the increase of Al doses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A decrease trend of body weight was observed in Alexposed rats, especially in 0.6% AlCl 3 group (no decrement of food intake) comparing with that of the control rats, which was consistent with previous reports (Hermenegildo et al, 1999;Jing et al, 2004). Meanwhile, it was shown that hippocampus, brain coefficients and hippocampus/ brain ratio in Al-exposed rats reduced gradually with the increase of Al doses.…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that Al deposited in the brain could impair the configuration of synapse, postsynaptic membrane and PSD which reflected the synaptic organization and metabolism (Jing, 2004). Especially, the thickness of the PSD represented synaptic efficacy (Jing, 2004); synaptic curvature reflected a morphological index of synaptic plasticity representing the different function of synapses such as the neuron transmitter release signs and the configuration changes in postsynaptic receptors (Markus and Petit, 1989). Subtle changes in synaptic structure can alter biophysical properties of synapses (Tang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrate that AlCl 3 induces toxic fibrillar Aβ aggregation in cortex and hippocampus of mice brain. Moreover documented reports denote that aluminium was specifically deposited in cortex and hippocampal regions of AD patients and also in rodents exposed to aluminium [33,34,35]. These reports support documented report denotes that Amyloid-β 42 induces neuronal cell death via ASK-1 [36] and JNK activation [37].…”
Section: Discussionsupporting
confidence: 84%
“…In recent studies, aluminium-induced degradation in the ability to learn and memorize was linked to the configurational changes in synapse [250,251]. The observed abnormal synaptic ultrastructure was characterized by a reduction in the thickness of postsynaptic density, enlargement of synaptic cleft and attenuation of synaptic curvature (Table 9).…”
Section: Synaptic Strengthmentioning
confidence: 95%